MENINGKATKAN PEMBELAJARAN PASSING SEPAK BOLA MELALUI PERMAINAN BOGET - Mansyah Rudin Subarkah (Musamus Journal of Physical Education and Sport (MJPES), 2019)
This study aims to improve the learning outcomes of passing soccer withmodifications to the Boget game. This research is a classroom action research conducted in 2cycles, each cycle consisting of 2 meetings. The place of research was conducted in Merauke3 Public High School. The subjects of this study were students of class X MIPA 4 in SMA N3 Merauke, totaling 29 students, consisting of 14 male students and 15 female students. Theresearch instruments used were: the format of aspects of the assessment of affective aspects,LKS, the format for evaluating psychomotor aspects. The results showed that the applicationof Boget game modification could improve the results of passing soccer learning in class XMIPA 4 SMA N 3 Merauke, which was marked by an increased understanding of studentlearning outcomes in each cycle. In the first cycle the average value of student learningoutcomes is complete at 31.03% which is in the interval 64-74 quite good category. In thesecond cycle the average value of student learning outcomes increased completely by 89.65%which was in the interval of 86-100 very good categories.